Численный анализ внешних течений вязкой жидкости (приближение озеена) методом r-функций - Ламтюгова, С. Н. (ХНУРЕ, 2012)
he slow flows of a viscous incompressible fluid around the infinite cylinder are treated in the paper. For the mathematical description of the current the Oseen linearization is used. For the numerical analysis of the flow it is offered to apply the R-functions method in a combination with the projective Galerkin Petrov method. The computational experiment has been conducted for the elliptical cylinder.
Keywords: приближение Озеена; метод R-функций; эллиптический цилиндр